ПРОСТРАНСТВЕННО-ВРЕМЕННОЕ ИЗМЕРЕНИЕ СОБЫТИЯ ЛЮБВИ - ИВАНЕНКО, Н. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
В статье анализируется событие любви в пространственно-временном измерении.Рассматриваются этапы трансформации события любви, которые свидетельствуют отом, что событие любви разворачивается во времени. На основании того, что событиелюбви и социокультурные трансформации цивилизаций разворачиваются в пространстве ивремени, в пространстве смыслов, высказывается предположение о возможности иханалогического сравнения.Іваненко Н. А. ПРОСТОРОВО-ЧАСОВИЙ ВИМІР ПОДІЇ ЛЮБОВІ В статтіаналізується подія любові в просторово-часовому вимірі. Розглядаються етапитрансформації події любові, які свідчать про те, що подія любові розгортається в часі. Напідставі того, що подія любові та соціокультурні трансформації цивілізацій розгортаютьсяв просторі та часі, в просторі сенсів, висловлюється припущення про можливість їханалогічного порівняння.Ключові слова: любов, подія любові, сенс, духовність, простір, час.Ivanenko N.A. SPATIO-TEMPORAL DIMENSION OF THE LOVE EVENT In this article thelove event is analyzed in existential dimension. Stages of transformation of the event of love whichtestify that love event develop in time are considered. On the basis of that the event of love and socialand cultural transformations of civilizations both develop in space and time, in space of senses theassumption of possibility of their analogical comparison comes out.Key words: love, event of love, sense, spirituality, space, time.